Evaluation of Production Efficiency in Asphalt Mixing Plant Using Lean Concept Based on TIMWOOD - Putra, Dio Adelian; Devia, Yatnanta Padma; Harimurti, Harimurti (AIBPM Publisher, 2024)
This study aims to assess the effectiveness of the lean concept in improving production efficiency in an asphalt mixing plant. The research emphasizes the need to reduce waste by applying the TIMWOOD principles, which target minimizing transportation, inventory, motion, waiting, overproduction, overprocessing, and defects. By identifying and eliminating non-value-adding activities, this study seeks to enhance overall production efficiency and resource utilization. The findings reveal significant efficiency improvements, with a 50% reduction in average processing time and a 46.14% decrease in total processing time after implementing the lean concept. These results demonstrate that the lean approach enhances productivity by optimizing production time, reducing operational waste, and improving workflow efficiency. Furthermore, the research underscores the practical implications of adopting lean principles, suggesting they can be a sustainable strategy for asphalt plants to boost operational efficiency, decrease production costs, improve resource allocation, and strengthen competitiveness in the industry. This study provides actionable insights for industries aiming to implement lean manufacturing concepts effectively